Properties of Reactive Powder Concrete and Its Application in Highway Bridge - Junwei Song; Shuhua Liu (Advances in Materials Science and Engineering)
A high-performance reactive powder concrete (RPC) was prepared with river sand, and the maximum particle size is 1.25 mm, under the 80°C steam curing condition. It is tested completely in terms of strength, uniaxial compressive stress-strain relation, flexural load-deflection relation, and frost resisting durability, and the results indicate that the concrete is suitable to RPC200. The uniaxial compressive stress-strain curve shows a linear-elastic behaviour up to explosive failure, which is different from that of conventional concrete. High postpeak load carrying capacity shows high toughness and reinforcing effect of the steel fibers. The RPC has not only much higher limit strain than conventional concrete, but also excellent frost resisting durability at the fifth day of age exceeding F300. Furthermore, the RPC satisfactorily meets the requirement of practical application for Xialouzi Bridge built with the RPC totally according to the calculation with finite element analysis software MIDAS/Civil. And the static loading testing result suggests that design of the bridge meets the utilization requirements.